Possibilities of increasing the physical health status of students different modes of racing loads - T.B. Serorez (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to substantiate theoretically and experimentally verify technology aimed at improving the process of university students in extracurricular athletics. Material : the study involved 413 male students aged 21-23 years. Results : organize and compile materials 26 references, extracurricular training program designed jogging, investigated the level of aerobic and anaerobic productivity first men of mature age, experimentally proved improving technologies for university students on the basis of cross-country use loads. Investigation of the influence of cross-country training of different directions on aerobic and anaerobic performance of the body indicates the advantage of cross-country loads that stimulate anaerobic energy processes. Confirmed the close correlation between aerobic and anaerobic performance and endurance of the organism, which gives grounds to consider the latter as one of the main components of physical fitness. Found that the relationship of aerobic and anaerobic capacity of the organism to other quality parameters of motor activity is weak or absent. Conclusions : it was found that the effectiveness of training depends on the energy of work and energy.